PENGARUH E-SERVICE QUALITYAPLIKASI KAI ACCESSTERHADAP KEPUTUSAN PEMBELIAN ULANG TIKET KERETA API PRAMEKS - Erika Fitri Sadewi (STIE Rajawali Purworejo, 2023)
This research aims to determine the influence of e-service quality on the decision to repurchase Prameks train tickets. The population in this study were KAI Access users who bought Prameks train tickets. The sampling technique in this study used purposive random sampling. The number of samples in this study was 96 people. The data analysis technique uses simple linear regression analysis, coefficient of determination test, t test which is processed using SPSS version 25. The results of the research show that the simple regression equation Y= 3.859+0.961X results in a constant coefficient of 3.859. The results of the price coefficient of determination show that the contribution of the e-service quality variable is 57.4%, while 46.2% is influenced by other variables not studied. Based on the t test, the e-service quality variable shows that Ho is rejected and Ha is accepted because the significance value obtained is (0.000 < 0.05).